2017
DOI: 10.1590/s1806-92902017000500001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ractopamine on Nile tilapia in the end of grow-out period

Abstract: -This experiment was conducted in outdoor tanks to evaluate the effect of inclusion of ractopamine at increasing levels (0, 4, 8, 12, and 16 mg kg −1 ) as additive in Nile tilapia (Oreochromis niloticus) diet in the final grow-out period (750-920 g) during 31 days. Therefore, 400 fish were housed into 20 experimental tanks, in a completely randomized design with five treatments and four replications. Growth performance, body yield, and chemical composition of fish muscle and organs were evaluated. Fish fed die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…They promote an increase in muscle protein deposition and a decrease in fat accumulation in some fish species such as Ictalurus punctatus (Rafinesque) (Mustin & Lovell 1993, 1995, Oncorhynchus mykiss (Walbaum) (Moccia et al 1998, Jalali et al 2010. Few reports are available using Nile tilapia (Oreochromis niloticus) (Mundim et al 2016, Tovo-Neto et al 2017).…”
Section: __________________ Corresponding Editor: Alvaro Bicudomentioning
confidence: 99%
“…They promote an increase in muscle protein deposition and a decrease in fat accumulation in some fish species such as Ictalurus punctatus (Rafinesque) (Mustin & Lovell 1993, 1995, Oncorhynchus mykiss (Walbaum) (Moccia et al 1998, Jalali et al 2010. Few reports are available using Nile tilapia (Oreochromis niloticus) (Mundim et al 2016, Tovo-Neto et al 2017).…”
Section: __________________ Corresponding Editor: Alvaro Bicudomentioning
confidence: 99%
“…Despite the regularization of the use of RAC as an additive in swine feed in more than 20 countries, especially the United States and Brazil, for aquatic organisms there is still no regulation of the use of RAC as a food additive. However, some studies have shown that the use of RAC in food improves productive performance and body composition, promoting an increase in muscle protein deposition and a decrease in fat accumulation in some sh species such as Ictalurus punctatus (Ra nesque) (Mustin and Lovell 1993;Mustin and Lovell 1995), Oncorhynchus mykiss (Walbaum) (Haji-abadi et al 2010;Moccia et al 1998), and also few reports are available using Nile tilapia (Mundim et al 2016;Tovo-Neto et al 2017).…”
Section: Introductionmentioning
confidence: 99%